The Narrowest Path : Antinomies of Self-Determination in Four Aesthetic Studies - Mehrgan, Omid (Historical Materialism Book Series, 2025)
A strategic reconstruction of modern German thought from the standpoint of aesthetic theory, The Narrowest Path reveals the characteristically modern, revolutionary project of freedom-as-autonomy to be unresolvably antinomic. Basing himself on four seminal texts by Kleist, Hegel, Marx, and Adorno, Mehrgan develops four basic figures: the literary, the person, the republic, and the artwork. All flourished during the long period between the French Revolution and the aftermath of the Second World War in Europe. The key antagonist is the rule of capital, paradoxically enabling self-determination and thwarting it. Still present in contemporary revolutionary experiments, this daunting conflict, the book argues, shows itself best in the aesthetic - but the resolution lies elsewhere. See Less